An assessment of corporate social responsibility of property developers in Bauchi Metropolis, Nigeria - Tukur, Sadiq; Shehu, Jamilu; Mammadi, Abubakar; Sulaiman, Ummi Aliyu (Goodwood Publishing, 2019)
Purpose: The study aims to assess the corporate social responsibility of property developers in Bauchi metropolis with a view to examine the importance and effects of corporate social responsibility on property development in the study area. This study is limited to Bauchi metropolis. Research Methodology:The study uses descriptive and exploratory research design using quantitative research approach. Questionnaires were administered to 20 property developers within Bauchi metropolis using purposive sampling techniques. Reliability was investigated by an overall average Cronbach’s Alpha value of 0.81, the data obtained was analyzed using percentage computation, weighted mean, relative importance index (RII) and severity index (SI) were also used. Findings: The most important corporate social responsibility (CSR) to the property developers is environmental sustainability followed by a qualitative environment, the less important is the safety of houses. Furthermore, the highest CSR provided by the developers is environmental sustainability. Among the highest effects of neglecting corporate social responsibility is causing damage to the environment while the least is developing poor neighborhoods. Limitations: This study explored on only 20 property development firms within Bauchi metropolis, results might not necessarily apply to other firms within the metropolis. Contribution: This study will be of significant importance to the government and professional bodies in the built environment in terms of policy formulation, these can help checkmate the property development companies in carrying out corporate social responsibilities to the immediate environment they operate thereby becoming socially responsible and allowing the general public/community to enjoy projects that will enhance their lives. Keywords:Corporate social responsibility, Sustainable development, property developers